Biofuels and family farming in Uruguay: A feasible alliance? - Carámbula, Matías; Chiappe, Marta; Fernández, Emilio; Figueredo, Soledad (Agrociencia Uruguay, 2011)
The global energy crisis caused by high levels of fossil fuels consumption and the signs of oil depletion explain the search for alternative energy to traditional sources. Progress towards bio-fuels policy is positioned in a central place in Uruguay’s political agenda. This context converges with a scenario of expansion of agricultural activity, marked by a dynamism based on the domestic economic environment changes, and major transformations in the productive base. In this context, in order to assess the social impacts resulting from the expansion of crops for energy purposes, this research was carried out. It explores the social impact of biofuels production in Uruguay taking as a reference the situation of family farm production. It assumes that the demand of land for energy crop production puts pressure on other production systems. Related to this, it is possible to establish a continuum between a view that holds that family farms are marginal to biofuel production, and an inclusive view which encourages the incorporation of family farmers into national production chains. In this scenario, the paper attempts to provide elements to answer the question about whether this new line of national production generates opportunities or threats to family farming.